Composite positive electrode current collector, electrode tab, and secondary battery
Patent Information
- Application Number
- CN202180089972.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-10-08
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2041-10-08
AI Technical Summary
但是,锂离子二次电池的长循环寿命化是永恒的课题
[0046]本发明通过具有上述构成,能够防止或降低由电解液或空气中的水分导致的保护层发生破坏或者吸水劣化,提高复合正极集流体中各层之间的结合力,防止导电层脱落,增强复合正极集流体以及极片自身的机械强度,提高集流体的循环寿命。
Smart Images

Figure CN116745940B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary battery technology, and more particularly to a composite positive electrode current collector containing graphene, as well as an electrode and a secondary battery using the current collector. Background Technology
[0002] Lithium-ion rechargeable batteries are widely used in electric vehicles and consumer electronics due to their advantages such as high energy density, high output power, and low environmental pollution. However, extending the cycle life of lithium-ion rechargeable batteries remains a persistent challenge.
[0003] Existing composite current collectors are typically formed by sequentially stacking an insulating layer, a protective layer, and a conductive layer (CN109873165A). In these composite current collectors, the shedding of the conductive layer is one of the reasons that seriously hinders the long cycle life of secondary batteries. Summary of the Invention
[0004] The problem that the invention aims to solve
[0005] The problem to be solved by the present invention is to prevent or reduce the damage or deterioration of the protective layer caused by moisture in the electrolyte or air, improve the bonding force between the layers in the composite positive current collector, prevent the conductive layer from falling off, and enhance the mechanical strength of the composite positive current collector and the electrode itself, thereby affecting the cycle life.
[0006] Specifically, through continuous exploration, the inventors discovered that during the electrode fabrication process, when cold-pressing the composite current collector to form the electrode, both the active material and the composite current collector undergo a certain degree of elongation under pressure. The inconsistent elongation rates of the insulating layer, conductive layer, and protective layer lead to microcracks in the conductive and protective layers of the composite current collector. After electrolyte injection and complete wetting of the electrode, these microcracks increase the contact area between the electrolyte and the protective layer. In positive electrode current collectors with a protective layer composed of metal oxides, the protective layer can undergo side reactions with corrosive substances in the electrolyte, causing damage to the protective layer. This affects the bonding strength between the protective layer and the conductive and insulating layers, leading to conductive layer detachment during use and impacting cycle life.
[0007] In addition, the inventors have also discovered that if the humidity in the manufacturing environment exceeds the standard during the manufacturing of composite current collectors, the oxide of the protective layer will absorb moisture, affecting the deposition of the conductive layer on the protective layer, which in turn affects the bonding force between the protective layer and the conductive and insulating layers, and will also cause the conductive layer to fall off during the use of the electrode, affecting the cycle life.
[0008] Technical solutions for solving the problem
[0009] This application is made in view of the above-mentioned technical problems, and its purpose is to provide a composite positive current collector that can prevent or reduce the damage or deterioration of the protective layer caused by moisture in the electrolyte or air, improve the bonding force between the layers in the composite current collector, especially the composite positive current collector, prevent the conductive layer from falling off, and enhance the mechanical strength of the composite positive current collector and the electrode itself, thereby achieving a long cycle life.
[0010] To achieve the above objectives, a first aspect of this application provides a composite positive current collector, wherein a protective layer, a graphene metallization layer, and a conductive layer are sequentially disposed on the surface of an insulating layer; the protective layer is composed of a metal oxide, and the graphene metallization layer contains highly reduced graphene oxide with oxygen-containing organic groups.
[0011] Therefore, it is possible to prevent or reduce the damage or deterioration of the protective layer caused by moisture in the electrolyte or air, improve the bonding force between the layers in the composite positive electrode current collector, prevent the conductive layer from falling off, and enhance the mechanical strength of the composite positive electrode current collector, thereby improving cycle life.
[0012] In a preferred embodiment, the above-mentioned high-reduction graphene oxide is composed of graphene with two to six layers.
[0013] This allows for a better balance between material conductivity and the number of functional groups, as well as the adjustment of the number of covalent bonds, resulting in a more coherent gradient change in interlayer parameters.
[0014] In a preferred embodiment, the oxygen-containing organic group comprises at least one of hydroxyl, aldehyde, ketone, carboxyl, and ether groups.
[0015] Therefore, the original composite positive electrode current collector protective layer and conductive layer can be upgraded from intermolecular bonding to intermolecular bonding, which significantly improves the interlayer bonding force and prevents the conductive layer from falling off.
[0016] In a preferred embodiment, the thickness of the above-mentioned highly reduced graphene oxide is 0.5 nm to 7 nm, optionally 0.6 nm to 5 nm, and more preferably 0.7 nm to 3.5 nm.
[0017] Therefore, it can effectively balance coating and dispersibility in liquids with final thermal conductivity, electrical conductivity and hydrophobicity.
[0018] In a preferred embodiment, when performing Raman spectroscopy on the above-mentioned highly reduced graphene oxide, the target value is 1200 cm⁻¹. -1 Up to 1400cm -1 Characteristic peak D was observed at 1500 cm⁻¹. -1 Up to 1600cm -1A characteristic peak G was observed, and the ratio of the intensity I(D) of the characteristic peak D to the intensity I(G) of the characteristic peak G, I(D) / I(G), was less than 1.2.
[0019] Therefore, it can effectively balance coating and dispersibility in liquids with final thermal conductivity, electrical conductivity and hydrophobicity.
[0020] In a preferred embodiment, the contact angle of the high-reduction graphene oxide with water is 90° or higher.
[0021] Therefore, it can effectively balance coating and dispersibility in liquids with final thermal conductivity, electrical conductivity and hydrophobicity.
[0022] In a preferred embodiment, the electron mobility of the aforementioned highly reduced graphene oxide at room temperature is 1 × 10⁻⁶. 4 ~1×10 5 cm 2 / (V·s).
[0023] Therefore, good electrical conductivity can be obtained.
[0024] In a preferred embodiment, the thermal conductivity of the aforementioned highly reduced graphene oxide is 2 × 10⁻⁶. 2 ~9×10 4 W / (m·K); 8×10 2 ~1×10 4 W / (m·K), or 2×10 3 ~9×10 3 W / (m·K).
[0025] Therefore, good thermal conductivity can be obtained.
[0026] In a preferred embodiment, the specific surface area of the aforementioned highly reduced graphene oxide is 50–1000 m². 2 / g, which can be selected from 100 to 800m 2 / g, or 140~700m 2 / g.
[0027] This allows for good adhesion between the protective layer and the underlying insulating layer.
[0028] In a preferred embodiment, the fracture strength of the above-mentioned highly reduced graphene oxide is 20-110 GPa, optionally 30-100 GPa, and more preferably 40-80 GPa.
[0029] This results in a composite material with good tensile strength, while also exhibiting excellent toughness, flexibility, and ductility.
[0030] In a preferred embodiment, the metal oxide of the protective layer comprises at least one of aluminum oxide, cobalt oxide, chromium oxide, and nickel oxide.
[0031] In a preferred embodiment, the conductive layer comprises a metallic conductive material, which may be selected from at least one of aluminum, copper, nickel, titanium, silver, nickel-copper alloy, and aluminum-zirconium alloy.
[0032] In a preferred embodiment, the insulating layer comprises an organic polymer insulating material, optionally including at least one of polyamide, polyterephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polybutylene terephthalate, poly(p-phenylene terephthalamide), polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber, and polycarbonate.
[0033] In a preferred embodiment, the graphene metallization layer is formed by coating a slurry containing highly reduced graphene oxide and a binder using one or more methods, including gravure coating, spraying, and immersion. The binder comprises one or more of glycidyl methacrylate, polyvinylidene fluoride, styrene-butadiene rubber latex, polytetrafluoroethylene, polyolefin, polyimide, and polyurethane. The solid content of the slurry is 5% to 30% by weight, and the proportion of highly reduced graphene oxide in the solid content is 10% to 35% by weight.
[0034] Therefore, it is possible to easily obtain a graphene metallized layer with good adhesion to the protective layer.
[0035] In another embodiment, an electrode is provided, which includes the aforementioned composite positive current collector.
[0036] This allows for the production of electrodes with long cycle life.
[0037] In another embodiment, a secondary battery is provided, which includes the aforementioned electrode.
[0038] This allows for the production of rechargeable batteries with long cycle life.
[0039] In another embodiment, a battery module is provided, which includes the aforementioned secondary battery.
[0040] This allows for the creation of battery modules with long cycle life.
[0041] In another embodiment, a battery pack is provided, which includes the battery module described above.
[0042] This allows for the creation of battery packs with long cycle life.
[0043] In another embodiment, an electrical device is provided, including at least one selected from the above-described secondary battery, the above-described battery module, or the above-described battery pack.
[0044] This allows for the creation of electrical devices with long cycle lifespans.
[0045] Invention Effects
[0046] By having the above-described structure, the present invention can prevent or reduce the damage or deterioration of the protective layer caused by moisture in the electrolyte or air, improve the bonding force between the layers in the composite positive electrode current collector, prevent the conductive layer from falling off, enhance the mechanical strength of the composite positive electrode current collector and the electrode itself, and improve the cycle life of the current collector. Attached Figure Description
[0047] Figure 1 This is a schematic diagram of the layered structure of a composite positive electrode current collector in existing technology.
[0048] Figure 2 This is a schematic diagram of the composite positive current collector according to a specific embodiment of this application.
[0049] Figure 3 This is the Raman spectrum of the highly reduced graphene oxide used in Example 03.
[0050] Figure 4 This is the Raman spectrum of the graphene used in Comparative Example 7.
[0051] Figure 5 It is the I(D) / I(G) value of the graphene used in Example 03 and Comparative Example 7.
[0052] Figure 6 This is a schematic diagram of a secondary battery according to one embodiment of this application.
[0053] Figure 7 yes Figure 6 An exploded view of a secondary battery according to one embodiment of this application is shown.
[0054] Figure 8 This is a schematic diagram of an electrical device that uses the battery pack from one embodiment of this application as a power source.
[0055] Figure 9 This is a cross-sectional SEM image of the composite positive current collector used in Example 03 after 1000 charge-discharge cycles.
[0056] Figure 10 This is a cross-sectional SEM image of the composite positive current collector used in Comparative Example 7 after 1000 charge-discharge cycles.
[0057] Symbol Explanation
[0058] 1: Battery module; 5: Secondary battery; 51: Housing; 52: Electrode assembly; 53: Top cover assembly; 101: Insulating layer; 102: Protective layer; 103: Graphene metallization layer; 104: Conductive layer. Detailed Implementation
[0059] The present application is further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the application. It should be clear that the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0060] The structure and performance of the current collector in one embodiment of this application are described in detail below.
[0061] In the composite positive current collector of this application, such as Figure 2 As shown, a protective layer, a graphene metallization layer, and a conductive layer are sequentially disposed on the surface of the insulating layer; the protective layer is composed of metal oxide, and the graphene metallization layer contains highly reduced graphene oxide, which has oxygen-containing organic groups.
[0062] The following provides a detailed explanation of each layer.
[0063] [Graphene metallization layer]
[0064] In the current collector of this application embodiment, the graphene metallization layer mainly serves to support and protect the conductive layer. The thickness D2 of the graphene metallization layer should be sufficient for the current collector to be used in the electrode, but preferably it satisfies 1nm ≤ D2 ≤ 200nm. The upper limit of D2 can be 200nm, 180nm, 150nm, 120nm, 100nm, 80nm, 60nm, 50nm, 40nm, 30nm, or 20nm, and the lower limit of D2 can be 1nm, 2nm, 5nm, 8nm, 10nm, 12nm, 15nm, or 18nm; the range of D2 can be any value from the upper or lower limit. If the graphene metallization layer is too thin, it cannot sufficiently strengthen the composite positive electrode current collector, and it is prone to breakage during electrode processing; if it is too thick, it will reduce the volumetric energy density of the battery using the current collector. Preferably, 5nm ≤ D2 ≤ 150nm; more preferably, 10nm ≤ D2 ≤ 100nm.
[0065] By placing a graphene metallization layer between the protective layer and the conductive layer, the following effects can be achieved.
[0066] First, the graphene metallization layer contains highly reduced graphene oxide, which has oxygen-containing organic groups. When used to connect the protective layer and the conductive layer, it can improve the bonding force between them. The mechanism is not yet clear, but it can be speculated that when highly reduced graphene oxide containing oxygen-containing organic groups such as hydroxyl, aldehyde, ketone, carboxyl, and / or ether groups is used to connect the metal oxide in the protective layer and the metal material in the conductive layer, covalent bonds such as -O-C-O-M (where M represents a metal atom) can be formed. Thus, the original composite positive electrode current collector protective layer and conductive layer can be upgraded from intermolecular bonding to interatomic bonding, significantly improving the interlayer bonding force and preventing the conductive layer from falling off.
[0067] Furthermore, by setting up a graphene metallization layer, it is possible to achieve a continuous gradient change in physical properties between the insulating layer, protective layer, graphene metallization layer, and conductive layer, avoiding abrupt changes in physical properties such as the direct transition from the insulating layer to the conductive layer. This results in a continuous and uniform distribution of forces across the multilayer structure of the composite positive electrode current collector, ensuring a strong bond at the interface during manufacturing and service.
[0068] Secondly, due to the hydrophobicity of highly reduced graphene oxide, it can inhibit the electrolyte from penetrating into the protective layer, thereby inhibiting the corrosion of the protective layer and preventing the conductive layer from falling off.
[0069] Furthermore, due to the high strength of highly reduced graphene oxide, the protective layer inside the current collector is less prone to microcracks when the electrode sheet containing it is cold rolled. Even when the electrolyte seeps in, it can reduce the contact area between the electrolyte and the protective layer, inhibit the corrosion of the protective layer, and prevent the conductive layer from falling off.
[0070] The preferred high-reduction graphene oxide is a treated high-reduction graphene oxide, which achieves a suitable degree of oxidation, better balancing the material's conductivity with the number of functional groups and covalent bonds, and realizing a more coherent gradient of interlayer parameters. This treated high-reduction graphene oxide is preferably graphene oxide that has undergone oxidation, purification, drying, and high-temperature reduction treatment. The high-temperature reduction conditions are, for example, reduction treatment at 250–450°C for 12–24 hours in the presence of a reducing agent.
[0071] The reducing agents mentioned above can be, for example, hydrazine and its derivatives.
[0072] Among these, the processed high-reduction graphene oxide is preferably a high-reduction graphene oxide with two to six layers. Too many layers result in excessive hydrophobicity, which can affect coating and dispersibility in liquids. Too few layers, on the other hand, fail to provide sufficient thermal conductivity, electrical conductivity, and ultimately, hydrophobicity.
[0073] As for highly reduced graphene oxide, its thickness is preferably in the range of 0.3–7 nm, more preferably 0.5–5 nm, and even more preferably 0.7–3.5 nm. Generally, while there is a certain correlation between the thickness and the number of layers in graphene, they are not entirely correlated. This is believed to be because different treatments of graphene result in variations in its oxidation degree and functional groups, leading to differences in intermolecular forces or molecular morphology between layers, thus causing a mismatch between thickness and the number of layers. If the thickness is too thick, the hydrophobicity becomes too strong, affecting coating and dispersibility in liquids. Conversely, if the thickness is too thin, sufficient thermal conductivity, electrical conductivity, and ultimate hydrophobicity cannot be achieved.
[0074] When performing Raman spectroscopy on highly reduced graphene oxide, at 1200 cm⁻¹ -1 Up to 1400cm -1 Characteristic peak D was observed at 1500 cm⁻¹. -1 Up to 1600cm -1 Characteristic peak G was observed, and the peak intensity ratio I(D) / I(G) of characteristic peak D to characteristic peak G is preferably 1.2 or less, more preferably less than 1.2. If this ratio is too high, it indicates more defects in the carbon atom crystal, which will affect the performance of the graphene material.
[0075] As a highly reduced graphene oxide, it is preferable that its contact angle with water is greater than 90°. If this contact angle is too small, the hydrophobicity is too low, and it cannot ensure sufficient protection against electrolyte penetration into microcracks.
[0076] As a highly reduced graphene oxide, an electron mobility of 1×10⁻⁶ at room temperature is preferred. 4 ~ 1×10 5 cm 2 / (V·s). When this electron mobility is too low, it will affect the conductivity of the composite current collector.
[0077] As a highly reduced graphene oxide, its thermal conductivity is 2×10⁻⁶. 2 ~9×10 4 W / (m·K); 8×10 2 ~1×10 4 W / (m·K), or 2×10 3 ~9×10 3 W / (m·K). If this thermal conductivity is too low, it will affect the heat transfer effect of the composite current collector.
[0078] As a highly reduced graphene oxide, it has a specific surface area of 50–1000 m². 2 / g, which can be selected from 100 to 800m 2 / g, or 140~700m 2 / g. When the surface area is too high, the high-reduction graphene oxide is prone to agglomeration, affecting its dispersion in liquid; when it is too low, it is not conducive to the adsorption force between the protective layer and the bottom insulating layer.
[0079] As a highly reduced graphene oxide, the tensile strength is 20–110 GPa, optionally 30–100 GPa, and even more preferably 40–80 GPa. If the tensile strength is too high, the overall toughness of the composite current collector is too strong, resulting in a low elongation; if it is too low, it fails to achieve the effect of strengthening the tensile strength of the composite current collector.
[0080] As a method for forming a graphene metallization layer on a protective layer, one example is to use a slurry containing highly reduced graphene oxide and a binder, and coat it onto the protective layer by one or more methods such as gravure coating, spraying, and immersion.
[0081] The binder may be one or more of glycidyl methacrylate, polyvinylidene fluoride, styrene-butadiene rubber latex, polytetrafluoroethylene, polyolefin, polyimide and polyurethane, and the solid content of the slurry may be 5% to 30% by weight, wherein the proportion of highly reduced graphene oxide in the solid content may be 10% to 35% by weight.
[0082] [Insulating layer]
[0083] In the current collector of this application embodiment, the insulating layer mainly serves to support and protect the conductive layer. The thickness D1 of the insulating layer only needs to be sufficient for the current collector to be used in the electrode, but preferably satisfies 1μm≤D1≤20μm. The upper limit of D1 can be 20μm, 15μm, 12μm, 10μm, or 8μm, and the lower limit of D1 can be 1μm, 1.5μm, 2μm, 3μm, 4μm, 5μm, 6μm, or 7μm; the range of D1 can be any value of the upper or lower limit. If the insulating layer is too thin, it is prone to breakage during electrode processing; if it is too thick, it will reduce the volumetric energy density of the battery using the current collector. Preferably, 2μm≤D1≤10μm; more preferably, 2μm≤D1≤6μm.
[0084] Optionally, the material of the insulating layer is selected from organic polymer insulating materials, inorganic insulating materials, and composite materials. More preferably, the composite material is composed of organic polymer insulating materials and inorganic insulating materials.
[0085] The organic polymer insulating material is selected from at least one of polyamide (PA), polyterephthalate (PET), polyimide (PI), polyethylene (PE), polypropylene (PP), polystyrene (PS), polyvinyl chloride (PVC), acrylonitrile-butadiene-styrene copolymer (ABS), polybutylene terephthalate (PBT), poly(p-phenylene terephthalamide) (PPA), epoxy resin, polyoxymethylene (POM), phenolic resin, polypropylene (PPE), polytetrafluoroethylene (PTFE), silicone rubber, polyvinylidene fluoride (PVDF), and polycarbonate (PC).
[0086] Among them, the inorganic insulating material is preferably at least one of alumina (Al2O3), silicon carbide (SiC), and silicon dioxide (SiO2).
[0087] The composite is preferably at least one of epoxy resin glass fiber reinforced composite material and polyester resin glass fiber reinforced composite material.
[0088] Preferably, the insulating layer is made of organic polymer insulating materials. Since the density of the insulating layer is typically lower than that of metal, the composite positive electrode current collector of this application can increase the gravimetric energy density of the battery. Furthermore, because the insulating layer provides good load-bearing and protection for the layers located on its surface, it is less prone to electrode breakage, a common phenomenon in traditional current collectors.
[0089] [Protective Layer]
[0090] The current collector of this application includes a protective layer disposed between the insulating layer and the graphene metallization layer.
[0091] The protective layer of this application can form a supporting structure to protect the insulating layer, thereby providing better protection and preventing the insulating layer from being oxidized, corroded, or damaged. Furthermore, the protective layer of this application can also improve the bonding force between the insulating layer and the graphene metallized layer, thereby improving the mechanical strength of the current collector.
[0092] The protective layer is made of metal oxide, preferably at least one of aluminum oxide, cobalt oxide, chromium oxide, and nickel oxide.
[0093] Because metal oxides have a larger specific surface area, the bonding force between the protective layer and the insulating layer of the metal oxide material is enhanced. At the same time, because metal oxides have a larger specific surface area, they can strengthen the bonding force between the metallized graphene layer and the insulating layer, thereby improving the overall strength of the current collector.
[0094] The thickness D3 of the protective layer only needs to be sufficient to allow the current collector to be used on the electrode, but preferably D3 satisfies the following conditions: D3 ≤ 1 / 10D4 and 1nm ≤ D3 ≤ 200nm, that is, the thickness D3 is less than or equal to 1 / 10 of the thickness of the conductive layer D4 and is within the range of 1nm to 200nm. The upper limit of the protective layer thickness D3 can be 200nm, 180nm, 150nm, 120nm, 100nm, 80nm, 60nm, 55nm, 50nm, 45nm, 40nm, 30nm, or 20nm, and the lower limit can be 1nm, 2nm, 5nm, 8nm, 10nm, 12nm, 15nm, or 18nm; the range of the protective layer thickness D3 can be any value from the upper or lower limit. If the protective layer is too thin, it will not be sufficient to protect the insulating layer; if the protective layer is too thick, its improvement on the mechanical strength and safety of the current collector will be limited, and it will instead reduce the weight energy density and volumetric energy density of the battery. Preferably, 10nm≤D3≤50nm, 10nm≤D3≤50nm.
[0095] The protective layer can be formed on the insulating layer by sputtering, in-situ formation, coating, etc. Magnetron sputtering is the preferred sputtering method. In-situ passivation, which forms a metal oxide passivation layer in situ on the metal surface, is the preferred in-situ formation method. One of the following coating methods is preferred: roll coating, extrusion coating, doctor blade coating, gravure coating, etc.
[0096] [Conductive layer]
[0097] In the current collector of this application embodiment, the thickness D4 of the conductive layer is sufficient to enable the current collector to be used as an electrode, but preferably satisfies: 300nm≤D4≤2μm.
[0098] The conductive layer is made of a metallic conductive material; preferably, it is made of at least one of aluminum, copper, nickel, titanium, silver, nickel-copper alloy, or aluminum-zirconium alloy.
[0099] In this embodiment, the thickness D4 of the conductive layer is sufficient to perform both conductivity and current collection, but preferably its upper limit is 2μm, 1.8μm, 1.5μm, 1.2μm, 1μm, or 900nm, and its lower limit is 800nm, 700nm, 600nm, 500nm, 450nm, 400nm, 350nm, or 300nm; the range of the conductive layer thickness D4 can be any value from the upper or lower limit. If the conductive layer is too thin, the conductivity and current collection effects will be poor, the battery polarization will be large, and it will be prone to damage during electrode processing, etc. If the conductive layer is too thick, it will affect the battery's gravimetric energy density and reduce the resistance of the current collector, thus hindering the improvement of battery safety performance. Preferably, 500nm ≤ D4 ≤ 1.5μm.
[0100] The conductive layer can be formed on the graphene metallization layer by at least one of mechanical rolling, bonding, vapor deposition, and chemical plating. The vapor deposition method is preferably physical vapor deposition (PVD). The physical vapor deposition method is preferably at least one of evaporation and sputtering. The evaporation method is preferably at least one of vacuum evaporation, thermal evaporation, and electron beam evaporation (EBEM). The sputtering method is preferably magnetron sputtering.
[0101] Another embodiment of the present invention uses a positive electrode sheet employing the aforementioned composite positive current collector. The structure and performance of this positive electrode sheet are described in detail below.
[0102] The positive electrode sheet includes the aforementioned composite positive current collector and a positive electrode film layer containing positive active material disposed on at least one surface of the composite positive current collector.
[0103] The positive electrode active material can be any positive electrode active material known in the art for use in batteries. As an example, the positive electrode active material may include at least one of the following materials: lithium phosphates with an olivine structure, lithium transition metal oxides, and their respective modified compounds. However, this application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Examples of lithium transition metal oxides include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, and lithium nickel cobalt manganese oxides (such as LiNi). 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also known as NCM) 333 LiNi 0.5 Co 0.2 Mn 0.3 O2 (also known as NCM) 523 LiNi 0.5 Co 0.25 Mn 0.25 O2 (also known as NCM) 211 LiNi 0.6 Co 0.2 Mn 0.2 O2 (also known as NCM) 622 LiNi 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM) 811 ), lithium nickel cobalt aluminum oxide (such as LiNi) 0.85 Co 0.15 Al 0.05At least one of O2 and its modified compounds. Examples of lithium phosphates with an olivine structure include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), lithium iron phosphate and carbon composites, lithium manganese phosphate (such as LiMnPO4), lithium manganese phosphate and carbon composites, lithium manganese iron phosphate, and lithium manganese iron phosphate and carbon composites.
[0104] The positive electrode film may also optionally include a binder and a conductive agent.
[0105] The positive electrode sheet can be prepared by dispersing the above-mentioned components used to prepare the positive electrode sheet, such as positive active material, conductive agent, binder and any other components, in a solvent (e.g. N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry onto the above-mentioned composite positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0106] Another embodiment of the present invention is a secondary battery using the above-described positive electrode. The structure and performance of this secondary battery are described in detail below. Typically, a secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator.
[0107] [Negative electrode plate]
[0108] The negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector, the negative electrode film layer including a negative electrode active material. The negative electrode film layer is disposed on the surface of the negative current collector.
[0109] The negative electrode current collector can be a metal foil or a composite current collector. For example, copper foil can be used as the metal foil. The composite current collector may include a polymer material substrate and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0110] The negative electrode active material can be any negative electrode active material known in the art for use in batteries. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0111] The negative electrode film may also optionally include binders, conductive agents, and other additives.
[0112] The negative electrode sheet can be prepared by dispersing the above-mentioned components for preparing the negative electrode sheet, such as negative electrode active material, conductive agent, binder and any other components, in a solvent (e.g., deionized water) to form a negative electrode slurry; coating the negative electrode slurry onto the negative electrode current collector, and then obtaining the negative electrode sheet after drying, cold pressing and other processes.
[0113] [Electrolytes]
[0114] The electrolyte acts as a conductor of ions between the positive and negative electrodes. This application does not impose specific restrictions on the type of electrolyte; it can be selected according to requirements. For example, the electrolyte can be liquid, gel, or entirely solid.
[0115] [Isolation membrane]
[0116] The secondary battery also includes a separator. This application does not impose any particular limitation on the type of separator; any known porous separator with good chemical and mechanical stability can be selected.
[0117] The material of the separator can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator can be a single-layer film or a multi-layer composite film; there are no particular restrictions. When the separator is a multi-layer composite film, the materials of each layer can be the same or different; there are no particular restrictions.
[0118] Positive electrode, negative electrode and separator can be made into electrode assembly by winding process or stacking process.
[0119] The secondary battery may include an outer packaging. This outer packaging can be used to encapsulate the aforementioned electrode components and electrolyte. The outer packaging of the secondary battery can be a hard shell or a soft case.
[0120] This application does not impose any particular limitation on the shape of the secondary battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 6 This is an example of a square-structured secondary battery 5.
[0121] Reference Figure 7 The outer packaging may include a housing 51 and a cover 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover 53 can be placed over the opening to close the receiving cavity. A positive electrode, a negative electrode, and a separator can be formed into an electrode assembly 52 using a winding or stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. The secondary battery 5 may contain one or more electrode assemblies 52, which can be selected by those skilled in the art according to specific practical needs.
[0122] Another embodiment of the present invention is a battery module assembled from at least one secondary battery 5, wherein the specific number of secondary batteries 5 contained in the battery module can be selected according to the application and capacity of the battery module.
[0123] Another embodiment of the present invention is a battery pack using the above-described battery modules. This is a battery pack obtained by assembling one or more of the aforementioned battery modules.
[0124] Another embodiment of the present invention is an electrical device that uses the above-mentioned secondary battery, battery module or battery pack.
[0125] The aforementioned electrical devices include the secondary batteries, battery modules, or battery packs described in this application. These secondary batteries, battery modules, or battery packs can be used as power sources for the aforementioned electrical devices, or as energy storage units for them. The aforementioned electrical devices may include, but are not limited to, mobile devices (e.g., mobile phones, laptops), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks), electric trains, ships and satellites, energy storage systems, etc.
[0126] For the aforementioned electrical devices, secondary batteries, battery modules, or battery packs can be selected according to their usage requirements.
[0127] Figure 8 This is an example of an electrical device. The electrical device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. To meet the device's requirement for range at low temperatures, the secondary battery, battery module, or battery pack described in this application can be used.
[0128] In the composite positive electrode current collector, electrode sheet, secondary battery, battery module, battery pack and electrical device of the present invention, the graphene metallization layer is provided between the protective layer and the conductive layer in the composite positive electrode current collector, which enhances the bonding force of each layer in the composite positive electrode current collector, thereby improving their respective cycle life.
[0129] Example
[0130] The present invention will now be illustrated with examples.
[0131] 1. Preparation of composite positive electrode current collector:
[0132] The composite positive current collector of the present invention is formed in the following manner. The parameters of the resulting composite positive current collector are shown in Table 1 below.
[0133] 1.1 Formation of the protective layer
[0134] The protective layer can be formed on a conventional insulating layer using methods such as vapor deposition, in-situ formation, and coating. For vapor deposition, physical vapor deposition (PVD) is preferred; PVD is further preferred to be at least one of evaporation and sputtering; evaporation is preferred to be at least one of vacuum evaporation, thermal evaporation, and electron beam evaporation (EBEM); and sputtering is preferred to be magnetron sputtering. For in-situ formation, in-situ passivation is preferred, i.e., a method of forming a metal oxide passivation layer in situ on the surface. For coating, roll coating, extrusion coating, blade coating, and gravure coating are preferred.
[0135] 1.2 Formation of graphene metallization layer
[0136] A slurry containing highly reduced graphene oxide and a binder is first applied to the protective or insulating layer by gravure coating, spraying, or immersion, and then dried to form a graphene metallization layer on the surface of the protective or insulating layer.
[0137] The coating process is as follows: High-reduction graphene oxide, binder, and NMP are stirred and mixed. Then, the slurry containing high-reduction graphene oxide and binder (glycidyl methacrylate) (solid content 5%–30% by weight, with high-reduction graphene oxide accounting for 10%–35% by weight of the solid content) is coated onto the sample surface. The coating thickness is controlled using a gravure roller, spray gun, or immersion method. Finally, it is dried at 60°C–120°C. This yields a graphene metallized layer. The specific solid content of the slurry and the drying temperature can be adjusted appropriately according to the viscosity required by the coating method.
[0138] 1.3 Formation of the conductive layer
[0139] The conductive layer can be formed on the graphene metallization layer or protective layer by at least one of the following methods: mechanical rolling, bonding, vapor deposition, and electroless plating. The preferred method for vapor deposition is physical vapor deposition (PVD). The preferred method for physical vapor deposition is at least one of evaporation and sputtering. The preferred method for evaporation is at least one of vacuum evaporation, thermal evaporation deposition, and electron beam evaporation (EBEM). The preferred method for sputtering is magnetron sputtering.
[0140] [Table 1]
[0141]
[0142] The specific parameters of the current collectors with graphene metallized layers are shown in Table 1. The thickness of each layer was measured by scanning electron microscopy (SEM) under standard testing conditions at a magnification of 30K. The number of layers in the high-reduction graphene oxide was determined by Raman spectroscopy using a 532nm laser with a wavenumber range of 800–3200. The I(D) / I(G) ratio was calculated by directly using the ratio of the intensities of the D and G peaks obtained from the Raman spectroscopy. The water contact angle was measured using a video optical contact angle measurement method based on droplet analysis, in accordance with national standard GB / T30693-2014. Electron mobility was determined using the Hall effect method, in accordance with standard Q / GZSPEI 30201100224-2018. Specific surface area was determined using the gas adsorption BET method (solid material specific surface area method), in accordance with national standard GB / T19587-2017. Tensile strength was determined by tensile strength testing at a tensile speed of 50 mm / min. Adhesive strength was also determined by tensile strength testing, in accordance with national standard GB / T The water content was determined by Karl Fischer liquid moisture test, with reference to standard HG / T 4067-2015. In addition, the solid content in the slurry was calculated based on the mass of each component used to make the slurry.
[0143] As shown in the table above, the composite current collector with the number C, which includes a graphene metallization layer, exhibits the best overall performance in terms of fracture strength, elongation, adhesion, and water content of the protective layer after 15 days.
[0144] [Table 2]
[0145]
[0146] As shown in the table above, the composite current collector with graphene metallization layer numbered C (Example 03) showed significant improvements in tensile strength, elongation, and water content of the protective layer after 15 days compared to the composite current collector numbered g (Comparative Example 7).
[0147] 1.4 Formation of Secondary Cells
[0148] Using the positive electrode shown in the table above, a secondary battery was manufactured by the following method.
[0149] Battery manufacturing:
[0150] Using conventional battery manufacturing processes, the positive electrode sheet (compacted density: 3.4 g / cm³) is... 3 ), PP / PE / PP separator and negative electrode sheet (compacted density: 1.6g / cm³) 3) They are wound together to form a bare cell, then placed into a battery casing, and an electrolyte (EC:EMC volume ratio of 3:7, LiPF6 of 1 mol / L) is injected. Then, sealing, formation and other processes are carried out to finally obtain a lithium-ion battery.
[0151] The cycle characteristics of the obtained secondary batteries were measured, and the results are shown in Table 3 below.
[0152] Battery testing methods:
[0153] The cycle life test for lithium-ion batteries is conducted using the following specific methods:
[0154] The lithium-ion battery was charged and discharged at two different temperatures: 25°C and 45°C. First, it was charged at 1C to 4.2V, and then discharged at 1C to 2.8V. The discharge capacity of the first cycle was recorded. Then, the battery was subjected to 1C / 1C charge-discharge cycles for 1000 cycles. The discharge capacity of the battery in the 1000th cycle was recorded. The discharge capacity of the 1000th cycle was divided by the discharge capacity of the first cycle to obtain the capacity retention rate in the 1000th cycle.
[0155] [Table 3]
[0156]
[0157] As shown in Tables 2 and 3 above, the embodiments of the present invention, by providing a graphene metallization layer between the protective layer and the conductive layer, improve the physical properties of the electrode and reduce cracking and microcracks generated after cold rolling and cycling, compared with the prior art. Furthermore, when the electrode using the current collector of the present invention is used in a battery, the battery characteristics are effectively improved, and the cycle life of the battery is significantly increased.
[0158] The current collectors in the batteries of Example 03 and Comparative Example 7 were removed after the cycle test, and their cross-sections were observed using SEM. Figure 9 , 10 As can be seen from this, the cross-section of Example 03 ( Figure 9 In Comparative Example 7, the conductive layer is firmly bonded to the protective layer via the graphene metallization layer, and no detachment of the conductive layer was observed. Figure 10 Significant shedding of the conductive layer is visible in the sample. This suggests that the improved battery cycle life in this embodiment stems from increased bonding strength between the layers in the current collector.
[0159] Although this application discloses preferred embodiments as described above, it is not intended to limit the claims. Any person skilled in the art can make several possible changes and modifications without departing from the concept of this application. Therefore, the scope of protection of this application should be determined by the scope defined in the claims of this application.
Claims
1. A composite positive electrode current collector, characterized in that, A protective layer, a graphene metallization layer, and a conductive layer are sequentially disposed on the surface of the insulating layer. The protective layer is composed of metal oxides, and the graphene metallization layer contains highly reduced graphene oxide with oxygen-containing organic groups.
2. The composite positive electrode current collector as described in claim 1, characterized in that, The high-reduction graphene oxide is composed of two to six layers of graphene.
3. The composite positive electrode current collector as described in claim 1, characterized in that, The oxygen-containing organic group includes at least one of hydroxyl, aldehyde, ketone, carboxyl, and ether groups.
4. The composite positive electrode current collector as described in any one of claims 1 to 3, characterized in that, The thickness of the highly reduced graphene oxide is 0.5 nm to 7 nm.
5. The composite positive electrode current collector as described in any one of claims 1 to 3, characterized in that, The thickness of the highly reduced graphene oxide is 0.6 nm to 5 nm.
6. The composite positive electrode current collector as described in any one of claims 1 to 3, characterized in that, The thickness of the highly reduced graphene oxide is 0.7 nm to 3.5 nm.
7. The composite positive electrode current collector as described in any one of claims 1 to 3, characterized in that, When performing Raman spectroscopy on the aforementioned highly reduced graphene oxide, the concentration was 1200 cm⁻¹. -1 Up to 1400cm -1 Characteristic peak D was observed at 1500 cm⁻¹. -1 Up to 1600cm -1 A characteristic peak G was observed, and the ratio of the intensity I(D) of the characteristic peak D to the intensity I(G) of the characteristic peak G, I(D) / I(G), was less than 1.
2.
8. The composite positive electrode current collector as described in any one of claims 1 to 3, characterized in that, The contact angle of the highly reduced graphene oxide with water is greater than 90°.
9. The composite positive electrode current collector as described in any one of claims 1 to 3, characterized in that, The high-reduction graphene oxide has an electron mobility of 1×10⁻⁶ at room temperature. 4 ~1×10 5 cm 2 / (V·s) 10. The composite positive electrode current collector according to any one of claims 1 to 3, characterized in that, The thermal conductivity of the highly reduced graphene oxide is 2 × 10⁻⁶. 2 ~9×10 4 W / (m·K).
11. The composite positive electrode current collector according to any one of claims 1 to 3, characterized in that, The thermal conductivity of the highly reduced graphene oxide is 8 × 10⁻⁶. 2 ~1×10 4 W / (m·K).
12. The composite positive electrode current collector according to any one of claims 1 to 3, characterized in that, The thermal conductivity of the highly reduced graphene oxide is 2 × 10⁻⁶. 3 ~9×10 3 W / (m·K).
13. The composite positive electrode current collector according to any one of claims 1 to 3, characterized in that, The specific surface area of the highly reduced graphene oxide is 50–1000 m². 2 / g.
14. The composite positive electrode current collector according to any one of claims 1 to 3, characterized in that, The specific surface area of the highly reduced graphene oxide is 100–800 m². 2 / g.
15. The composite positive electrode current collector according to any one of claims 1 to 3, characterized in that, The specific surface area of the highly reduced graphene oxide is 140–700 m². 2 / g.
16. The composite positive electrode current collector according to any one of claims 1 to 3, characterized in that, The fracture strength of the highly reduced graphene oxide is 20–110 GPa.
17. The composite positive electrode current collector according to any one of claims 1 to 3, characterized in that, The fracture strength of the highly reduced graphene oxide is 30–100 GPa.
18. The composite positive electrode current collector according to any one of claims 1 to 3, characterized in that, The fracture strength of the highly reduced graphene oxide is 40–80 GPa.
19. The composite positive electrode current collector as described in any one of claims 1 to 3, characterized in that, The metal oxide of the protective layer comprises at least one of aluminum oxide, cobalt oxide, chromium oxide, and nickel oxide.
20. The composite positive electrode current collector according to any one of claims 1 to 3, characterized in that, The conductive layer comprises a metallic conductive material, which includes at least one of aluminum, copper, nickel, titanium, silver, nickel-copper alloy, and aluminum-zirconium alloy.
21. The composite positive electrode current collector according to any one of claims 1 to 3, characterized in that, The insulating layer comprises an organic polymer insulating material, which includes at least one of polyamide, polyterephthalate, polyimide, polyethylene, polypropylene, polystyrene, polyvinyl chloride, acrylonitrile-butadiene-styrene copolymer, polypropylene, polyoxymethylene, epoxy resin, phenolic resin, polytetrafluoroethylene, polyvinylidene fluoride, silicone rubber, and polycarbonate.
22. The composite positive electrode current collector according to any one of claims 1 to 3, characterized in that, The graphene metallization layer is formed by coating a slurry containing highly reduced graphene oxide and a binder using one or more methods, including gravure coating, spraying, and dipping. The adhesive comprises one or more of glycidyl methacrylate, polyvinylidene fluoride, styrene-butadiene rubber latex, polytetrafluoroethylene, polyolefin, polyimide, and polyurethane. The slurry has a solid content of 5% to 30% by weight, and the high-reduction graphene oxide accounts for 10% to 35% by weight of the solid content.
23. An electrode sheet, characterized in that, It includes a composite positive current collector as described in any one of claims 1 to 22.
24. A secondary battery, characterized in that, It includes the electrode sheet as described in claim 23.
25. A battery module, characterized in that, Includes the secondary battery as described in claim 24.
26. A battery pack, characterized in that, Includes the battery module as described in claim 25.
27. An electrical appliance, characterized in that, It includes at least one selected from the secondary battery of claim 24, the battery module of claim 25, or the battery pack of claim 26.
Citation Information
Patent Citations
Current collector, pole piece and battery
CN109873165A
Positive electrode current collector and preparation method and application of positive electrode current collector
CN103515119A
Graphene oxide-bonded metal foil thin film current collector
CN109565053A
Current collector, pole piece thereof and electrochemical device
CN109873164A